Integrated Public Health Evaluation of Gut Microbiota, Inflammatory Biomarkers, and Nutritional Status in Patients Undergoing Colorectal Cancer Surgery - Adnan Ur Rehman, Manal Tariq, Fatima Rashid, Alina Mehwish, Muhammad Azhar Khan, Shehla Farhin (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Colorectal cancer (CRC) remains a major global health concern, with postoperative complications contributing significantly to morbidity and delayed recovery. Recent evidence suggests a close interrelationship between gut microbiota imbalance, systemic inflammation, and nutritional status influencing surgical outcomes. Objective: To assess the integrated role of gut microbiota composition, inflammatory biomarkers, and nutritional status in predicting postoperative complications among patients undergoing colorectal cancer surgery. Methods: A prospective observational study was conducted at the Department of Gastroenterology and Hepatology, MTI-Hayatabad Medical Complex, Peshawar, Pakistan, from June 2022 to March 2023. One hundred CRC patients scheduled for elective colorectal resection were enrolled. Preoperative stool samples were analyzed using 16S rRNA sequencing for microbial diversity. Serum CRP, IL-6, and TNF-α were measured by ELISA, while nutritional status was assessed using BMI and serum albumin levels. Postoperative outcomes were followed for 30 days. Statistical analyses were performed using SPSS v26, and multivariate regression identified predictors of complications. Results: Patients with gut dysbiosis (low Bifidobacterium and Lactobacillus) had significantly higher IL-6 and CRP levels (p < 0.001). Hypoalbuminemic patients (<3.5 g/dL) experienced more postoperative infections (28%) and longer hospital stays. IL-6, low albumin, and reduced microbiota diversity independently predicted complications. Conclusion: An integrated assessment of gut microbiota, inflammatory biomarkers, and nutritional health provides valuable predictive insight into surgical outcomes. Optimizing microbial balance, reducing inflammation, and improving nutrition before surgery may enhance recovery and reduce postoperative morbidity in colorectal cancer patients. Keywords: Colorectal cancer, Gut microbiota, Inflammatory biomarkers, IL-6, CRP, Nutritional status, Postoperative complications